On the Genesis and Significance of the Archean-hosted Carlow Castle Cu-Co-Au Deposit, Pilbara Craton, Western Australia - Fox, David Charles Mathieson (Curtin University, 2022)
This study provides the first analysis of and constraints on the genesis of the Carlow Castle Cu-Co-Au deposit in the Archean Pilbara Craton of NW Western Australia. Geochronological analyses constrain the deposit’s formation to 2.95 Ga, making it the oldest of its type on Earth. Sulfur isotope analysis and thermodynamic modelling suggest an oxidised source of ore-formation. This thesis also provides the first demonstration of the utility of Cu isotopes to understand Archean ore-forming processes.